Peran Hakim Agung, Metode Berfikir Juridik dan Konsep Keadilan dalam Spirit Reformasi - Mandala, Opan Satria; Husni, Anang; Efendi, Saparudin; Rahmatyar, Ana; Zubaedi, Zubaedi (Varied Knowledge Journal, 2025)
This article aims to find out the conception of Justice formulated by the Supreme Judge which is in accordance with the spirit of reform and the juridical-normative thinking method that can be used in formulating the conception of Justice and the role of the Supreme Judge in supporting the realization of legal reform in Indonesia. The type of research used is Normative legal research, normative legal research is research that examines vague norms, conflicting norms and empty norms. Meanwhile, the approach used is a conceptual approach, a statutory approach. The results of this paper show that the concept of justice formed in the Supreme Court's decision is Unity Justice, which is formulated based on: the value of justice that grows and develops in society, the norms of justice and applicable laws and regulations, the interests of achieving the goals of state life, and the interests of the development of community life and the normative juridical thinking method (even coupled with empirical) is not able to formulate complete justice (unity justice), therefore it is added with a holistic and integrative thinking approach and the role of the Supreme Judge in unifying or harmonizing the various dichotomies of the views of the parties that often lead to prolonged forms of conflict through a holistic and integrative approach.